Working Paper; Methodology Design; Meditation and Individual Job Performance - Itzchel SANCHEZ; Sergio ALVARADO; Ramon MARTINEZ; Juan C. NIEBLA; David MORENO; Patricia C INZUNZA (Communications of International Proceedings, 2023)
The purpose of this paper is to describe and explain the methodology used in the design of a quasi-experiment that was carried out in a private sector higher education institution in the city of Culiacan Sinaloa, Mexico. Research connecting OCB/CWB models with any type of meditation is almost non-existent. The purpose is to evaluate the changes experienced in civic behavior OCB and counterproductive behavior CWB of seventeen members of the university community after 90 days of meditation practice in sessions of 12 to 15 minutes. The quasi-experiment includes the participation of a control group which did not meditate during the period of the experiment. To evaluate the effect of meditation on the behavior of the participants, an information collection instrument was designed and applied at the beginning of the sessions and at the end of the experimental period. During this period, different techniques were used that had not been used together, which constitutes a methodological contribution to the analysis of the relationship between meditation and individual behavior in organizations.
Keywords: Meditation; quasi-experiment; Organizational Civic Behavior (OCB); Counterproductive Work Behavior (CWB).